2019
DOI: 10.1186/s12935-019-0830-1
|View full text |Cite
|
Sign up to set email alerts
|

H/ACA box small nucleolar RNA 7B acts as an oncogene and a potential prognostic biomarker in breast cancer

Abstract: Background Breast cancer (BC) is the most frequent malignancy occurring in women worldwide. Emerging evidence indicates that small nucleolar RNAs (snoRNAs) play a role in tumor development. In the current study, we evaluated expression profiles and functions of snoRNAs associated with BC. Methods We analyzed the expression levels of snoRNAs between breast cancer and normal tissues in TCGA database and found that SNORA7B is upregulated in BC. We confirmed this result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…We believe that SNORD63 and SNORD96A play crucial role in the tumorigenesis and development of ccRCC, but the underlying molecular mechanisms needs further studies to illuminate. As described above, snoRNAs are stably expressed and measurable in body fluids, empowering them the potential as biomarkers in various cancer types, such as NSCLC [16][17][18][19][20], CRC [21][22][23][24], breast cancer [25][26][27] and prostate cancer [28][29][30]. In current study, we demonstrated that SNORD63 and SNORD96A acted as the non-invasive diagnostic biomarkers for ccRCC even for early stage ccRCC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We believe that SNORD63 and SNORD96A play crucial role in the tumorigenesis and development of ccRCC, but the underlying molecular mechanisms needs further studies to illuminate. As described above, snoRNAs are stably expressed and measurable in body fluids, empowering them the potential as biomarkers in various cancer types, such as NSCLC [16][17][18][19][20], CRC [21][22][23][24], breast cancer [25][26][27] and prostate cancer [28][29][30]. In current study, we demonstrated that SNORD63 and SNORD96A acted as the non-invasive diagnostic biomarkers for ccRCC even for early stage ccRCC.…”
Section: Discussionsupporting
confidence: 52%
“…As described above, snoRNAs are stably expressed and measurable in body fluids, empowering them the potential as biomarkers in various cancer types, such as NSCLC [ 16 20 ], CRC [ 21 24 ], breast cancer [ 25 27 ] and prostate cancer [ 28 30 ]. In current study, we demonstrated that SNORD63 and SNORD96A acted as the non-invasive diagnostic biomarkers for ccRCC even for early stage ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…A single H/ACA small nucleolar RNA mediates tumor suppression downstream of oncogenic RAS, [56][57][58] and H/ACA box small nucleolar RNA 7B acts as an oncogene and a potential prognostic biomarker in breast cancer. 59 Our present results are consistent with these reports and provide novel evidence for an active role of CircMEG3 liver CSCs.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, our work suggests that H/ACA snoRNAs have higher propensity for upregulation in HGSC and are as such more likely to function as positive regulators of cancer cell proliferation and survival. This is consistent with earlier results linking the upregulation of SNORA7B with breast cancer (46) and SNORA42 in lung cancer (47). The link between the upregulation of H/ACA snoRNAs and poor prognosis was also observed in the case of non-small cell lung cancer, where expression of the H/ACA snoRNA binding protein Nop10 was found to drive tumorigenesis (48).…”
Section: Discussionsupporting
confidence: 91%